Music in the head : living at the brain-mind border - Rangell, Leo. (Karnac Books, 2009)
'We are starting to see a rapprochement between psychoanalysis and neuroscience such as Freud could only dream of. Pay dirt will be found at the brain-mind border. One can now perhaps hope to have an analysis of release hallucinations, equally rooted in neurology and psychiatry, in biology and biography. It is such a synthesis which Dr Leo Rangell, one of our most distinguished psychoanalysts, attempts here. As both subject and observer, Dr Rangell, trained in neurology and psychoanalysis, approaches his material with modesty and restraint, acutely aware of the dangers of over-inference and premature theorizing. And he does so in a style that is easy, unguarded, free of jargon, almost conversational.' Oliver Sacks, from the Foreword.